Growing Interest in Learning Class IXa Students at Smp Negeri 7 Sukabumi Through Optimizing Practicum Learning in The Laboratory - Murni Desi; Hidayati Herlina; Suhendar Suhendar (CV. Dharma Samakta Edukhatulistiwa, 2024)
The aim of the research is to foster students' interest in learning in Class IX A of SMP Negeri 7 Sukabumi City through optimizing learning in the laboratory. This experimental research was carried out in class IX A of SMP Negeri 7 Sukabumi City in 2024/2025, consisting of 28 students, 15 male students and 13 female students. This research was carried out for 13 days from August 8-20, 2024. The research results proved that